O sofrimento infantil : ouvindo crianças no serviço de saúde - Frizzera, Emília Helena da Silva (2012)
The paper is based on the observation of a multi professional team in the pediatrics ambulatory, of the University Hospital Cassiano Antonio de Moraes- Hucam, since 1997. We could see the growing number of children considered to have difficulties regarding learning and with depression and who were forwarded to clinics, what questioned us about who is the child with depression diagnosis, how does the child relate with family and school?, how does the child realize the events he/she is involved? Before that, the research aims at analyzing how the children with depression diagnosis realize and elaborate the events that compose their lives in the different space they circulate, especially, in the school environment. From a point of view that sees the man in a perspective of totality, inserted in a certain historical and cultural context and constituted by that context, the study intended to be away of a medicalized model, which works priority with bio physiological factors, minimizing the influence of social and historical aspects in the child’s health and welfare. For the research, a study case was done with children with depressive disorder diagnosis, who have been forwarded to be assisted by health services by the school or their own families. The research subjects were two children with depression diagnosis, 10 and 12 years old, period near teenage and considered to be risky in relation to outbreak and mental disorders, in some theories. When analyzing both subjects data, it was found the presence of complex ways of being, subjective constitutions marked by multiple events and by other people’s participation. The life of these children is composed by aspects, such as: to be an adopted child, illnesses and losses in the family environment, mistreating suffered in the family environment, the birth of a younger sibling and the limitation regarding the possibilities of making their own options. Although it is possible to establish relations with the school space, in this context, the family environment stands out along with its contradictions and possibilities in the development and expansion as well, in the life of these children. The paper highlights the importance of an interchange between education and health in order to respond the demands of life and health guarantee of the child in process of psychic suffering